Pengaruh Kecerdasan Emosi dan Kecerdasan Spiritual Terhadap Perilaku Prososial Siswa di SMA Negeri 9 Halmahera Selatan - Andris Noya (TANGKOLEH PUTAI, 2018)
This study aims to determine the effect of emotional intelligence and spiritual intelligence on prosocial behavior of students in South Halmahera 9 High School. The sample in this study were students of South Halmahera 9 High School, totaling 171 people. Data collection techniques are done by distributing questionnaires and interviews. The three questionnaires distributed were the emotional intelligence questionnaire, spiritual intelligence, and prosocial behavior. The collected data was analyzed using multiple linear regression analysis through the SPSS windows version 22.0 program. Through regression analysis the results show that emotional intelligence and spiritual intelligence have a significant positive effect on students' prosocial behavior (R2 = 0.587, Fcount = 119, 340; at a significance level of 0.000 <0.05).